Rabbit Population Dynamics: A Game-Based Learning Media for ‎Teaching Population Dynamics in Biology - Liah Badriah; Purwati Kuswarini Suprapto; Dani Ramdani (ISEJ : Indonesian Science Education Journal, 2026)
The integration of Information and Communication Technology (ICT) has encouraged the development of more interactive, contextual, and student-centered biology learning media. However, population dynamics remains a challenging topic for students because ecological interactions, such as population growth, predator–prey relationships, environmental carrying capacity, and resource availability, are abstract and cannot always be observed directly in classroom settings. This study aimed to design and evaluate the feasibility of Rabbit Population Dynamics (RPD), a game-based learning medium developed to support students’ understanding of population dynamics. This research and development study employed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation, integrated with Merrill’s principles of instruction to strengthen the pedagogical structure of the media. Product feasibility was examined through media expert validation, content expert validation, and a small-group trial involving 13 university students who had studied population dynamics. The results showed media validation of 87.90% in the highly feasible category, content validation of 93.90% in the highly feasible category, and a small-group trial score of 87.27% in the highly feasible category. These findings indicate that RPD is highly feasible as an interactive learning medium for the population dynamics subtopic. Further classroom implementation with high-school students is recommended to examine its effect on conceptual understanding, learning engagement, and problem-solving skills in biology learning.